2019
DOI: 10.1519/jsc.0000000000002353
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise Hypotension and Heart Rate Variability Responses Subsequent to Traditional, Paired Set, and Superset Resistance Training Methods

Abstract: The purpose of this study was to compare training volume, post-exercise hypotension (PEH) and heart rate variability (HRV) responses to different strength training methods. Thirteen trained men volunteered for this study. Three training methods were completed in a randomized design, which included: Traditional Set (TS) - three successive sets for the lying bench press (LBP), lat pulldown (LPD), incline 45° bench press (BP45), seated close-grip row (SCR), triceps extension (TE), and biceps curl (BC), with a 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
0
18
0
3
Order By: Relevance
“…The first phenomenon refers to afferent feedback of the baroreceptors that transmit peripheral information about the pressure that the plasma imposes in the blood vessels [21]. Although we did not measure participants' blood pressure, it is well reported that after a resistance exercise session (depending on the amount of muscle mass involved, volume, and training to or near to muscle failure), a decrease in blood pressure occurs [4,9,10]. This hypotensive effect may contribute to the reduction of the input from baroreceptors, favoring a decrease in cardiac parasympathetic activity and increased sympathetic nerve activity to maintain sufficient blood pressure for maintenance of vital functions (e. g., venous return) [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first phenomenon refers to afferent feedback of the baroreceptors that transmit peripheral information about the pressure that the plasma imposes in the blood vessels [21]. Although we did not measure participants' blood pressure, it is well reported that after a resistance exercise session (depending on the amount of muscle mass involved, volume, and training to or near to muscle failure), a decrease in blood pressure occurs [4,9,10]. This hypotensive effect may contribute to the reduction of the input from baroreceptors, favoring a decrease in cardiac parasympathetic activity and increased sympathetic nerve activity to maintain sufficient blood pressure for maintenance of vital functions (e. g., venous return) [21].…”
Section: Discussionmentioning
confidence: 99%
“…This hypotensive effect may contribute to the reduction of the input from baroreceptors, favoring a decrease in cardiac parasympathetic activity and increased sympathetic nerve activity to maintain sufficient blood pressure for maintenance of vital functions (e. g., venous return) [21]. Paz et al [4] evaluated RMSSD and blood pressure in response to the superset, paired set, and TRD systems, and reported reductions of all three experimental conditions. However, these findings are not universal [10], and further studies are needed to elucidate the relationship between these phenomena in response to resistance exercise sessions with different configurations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, there is also a controversy on which level of EP has a better protective effect on cardiac function [20]. It is still unclear which intensity or type of EP has the most significant protective effect on heart [21].…”
Section: Introductionmentioning
confidence: 99%
“…The loads for 10-RM were determined for each individual in the exercise leg extension (LE) (Leg Extension Machine, Technogym, made in Italy). The 10-RM test was performed following the protocol proposed by Paz et al [ 20 ] and Miranda et al [ 21 ]; The initial load was estimated according to the weight commonly used during resistance training sessions. The objective of the 10-RM test was to carry out 10 consecutive repetitions at a higher load.…”
Section: Methodsmentioning
confidence: 99%